An Exploration into Human Trafficking and Post-Trafficking from the Perspective of Relational Geography - Xue Rui; Chen Hui; Wei Lingling (Redai dili, 2022)
From the perspective of geography, human trafficking is the abnormal migration of a population. With the rise of the "relational turn" in human geography, relational geography provides a complex multidimensional and topological relationship logic system for studying human trafficking, which could help with exploring the process and correlation between the phenomenon and subjects of human trafficking. In this study, we focused on human trafficking aimed at women and young children and reviewed the relational geography theory to obtain the theoretical framework for this problem. Subsequently, we deconstructed the human trafficking and "post-trafficking" context from the paradigm of space, place, and subjectivity. Then, we constructed a relational geography logic system for the study and post-trafficking interventions. We found that (1) the connotations of "gender" and "body" in a patriarchal culture provide the "soil" and "market" for human trafficking aimed at women and young children. Because of its smallness on the spatial scale, the body is an important entrance to the study of human trafficking. Spatial physical disciplines and power separations exist in the relationship network formed by human trafficking. (2) Human trafficking generates multiple diachronic influences on victims. Children and women who have been abducted face the reconstruction of local relations and intersubjectivity during the post-trafficking stage. (3) Human trafficking governance and post-trafficking interventions should be conducted with a view toward the relational geography logic system and the paradigm of relational space, local relations, and intersubjectivity in order to open logical channels from offenders and victims. The introduction of relational geography may provide theoretical and practical contributions to the study of human trafficking. Regarding the former, it could promote the theoretical study of human trafficking crimes from the traditional paradigm of space to relationship space, as well as from the local to local relations and the subjective to intersubjectivity. In terms of application, findings of this study may draw attention to the importance of spatial physical discipline and power separation in human trafficking when strategizing regarding governance and interventions. Additionally, findings of the study may contribute to fostering more effective interventions during the post-trafficking stage because of our focus on the subjective reconstruction of women and children who have been kidnapped.